THE EFFECTIVENESS OF THE INDONESIAN FINANCIAL SERVICES AUTHORITY SUPERVISION ON SHARIA FINANCIAL INSTITUTIONS IN ACEH PROVINCE OF INDONESIA - Syariful Anami; Muhammad Iqbal; Riza Afrian Mustaqim (JURISTA: Jurnal Hukum dan Keadilan, 2025)
Aceh Province is the only region in Indonesia that has fully implemented an Islamic financial system, as outlined in Qanun Aceh Number 11 of 2018, concerning Islamic Financial Institutions. This regulation mandates all financial institutions operating in Aceh to comply with Sharia principles. However, the effectiveness of the Financial Services Authority (OJK) in supervising substantial adherence to Islamic jurisprudence (fiqh muamalah) remains questionable. This study aims to assess the efficacy of OJK’s supervision over Islamic financial institutions in Aceh and to identify the main obstacles and challenges in its implementation. The research employs an empirical, juridical, and statutory approach, with data collected through interviews, field observations, and a literature review. The findings reveal that OJK's supervisory role remains primarily administrative and has not adequately addressed the substantive aspects of Sharia compliance. Key obstacles include low Sharia literacy among industry players, weak roles of internal Sharia Supervisory Boards (DPS), limited human resources within OJK knowledgeable in Islamic finance, underutilised digital supervision systems, and weak institutional coordination. Based on Soerjono Soekanto's theory of legal effectiveness, all five components—legal substance, legal structure, legal culture, infrastructure, and community—are found to be insufficiently developed to support the ideal implementation of Islamic finance. The study recommends reformulating the supervisory approach to adopt a more participatory, contextual, and locally grounded model, ensuring the authentic and sustainable application of Islamic financial systems in Aceh